2018
DOI: 10.1055/s-0038-1668523
|View full text |Cite
|
Sign up to set email alerts
|

Apixaban versus Dalteparin for the Treatment of Acute Venous Thromboembolism in Patients with Cancer: The Caravaggio Study

Abstract: International and national guidelines recommend low-molecular-weight heparin for the treatment of venous thromboembolism (VTE) in patients with cancer. The aim of the Caravaggio study is to assess whether oral apixaban is non-inferior to subcutaneous dalteparin for the treatment of acute proximal deep vein thrombosis and/or pulmonary embolism in patients with cancer. The study is an investigator-initiated, multi-national, prospective, randomized, open-label with blind end-point evaluation (PROBE), non-inferior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
108
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(119 citation statements)
references
References 46 publications
1
108
0
3
Order By: Relevance
“…The mortality rate at 6 months was similar comparing apixaban with dalteparin (15.9 vs. 10.6%, HR 1.36, 95% CI 0.79-2.35). These results must be taken with caution and must await the final publication and the outcomes of Caravaggio trial [61] (NCT03045406), that will randomize 1168 patients to the same regimens of apixaban and dalteparin used in ADAM trial for 6 months. The primary outcome of the study is objectively confirmed recurrent VTE and this trial will be the largest trial ever performed in CAT treatment setting.…”
Section: Long-term Treatment Of Vte In Cancer Patientsmentioning
confidence: 99%
“…The mortality rate at 6 months was similar comparing apixaban with dalteparin (15.9 vs. 10.6%, HR 1.36, 95% CI 0.79-2.35). These results must be taken with caution and must await the final publication and the outcomes of Caravaggio trial [61] (NCT03045406), that will randomize 1168 patients to the same regimens of apixaban and dalteparin used in ADAM trial for 6 months. The primary outcome of the study is objectively confirmed recurrent VTE and this trial will be the largest trial ever performed in CAT treatment setting.…”
Section: Long-term Treatment Of Vte In Cancer Patientsmentioning
confidence: 99%
“…Ciononostante, nella pratica clinica oncologica è ancora diffuso l'impiego di eparina a basso peso molecolare, raccomandata dalle linee guida per la profilassi del tromboembolismo venoso nei pazienti oncologici, ma per la quale non sono disponibili in letteratura evidenze a supporto dell'efficacia nei pazienti con FA. Lo studio CARAVAGGIO, attualmente in corso, confronterà direttamente apixaban e dalteparina nel trattamento della trombosi venosa acuta prossimale e/o dell'embolia polmonare in soggetti oncologici, allo scopo di convalidare la terapia anticoagulante orale rispetto a quella parenterale in questa tipologia di pazienti [4]. Al momento in alcuni Centri vige la tendenza a utilizzare enoxaparina nella fase acuta della FA (in Pronto Soccorso), per poi valutare il pas-saggio a un diverso farmaco anticoagulante per la terapia cronica; in altri invece viene valutato da subito l'eventuale impiego di NOAC.…”
Section: Discussioneunclassified
“…The incidence of recurrent VTE was 0.7% with apixaban and 6.3% with dalteparin (HR, 0.099; 95% CI, 0.013‐0.780; P = .0281) . The CARAVAGGIO (apixaban for the treatment of venous thromboembolism in patients with cancer) trial, an investigator‐led, multinational, prospective, randomized trial that is currently ongoing, should provide further insight into the role of apixaban in the treatment of CAT . Table 6 summarizes the key characteristics and data from Hokusai‐VTE‐Cancer, SELECT‐D, and ADAM VTE studies.…”
Section: Evidence Base For the Use Of Rivaroxaban In Catmentioning
confidence: 99%
“…Further studies regarding extended‐duration CAT treatment would be beneficial but will likely continue to be challenging to obtain. The upcoming DOAC studies for the treatment of CAT—CARAVAGGIO and CONKO‐011 (Rivaroxaban in the Treatment of VTE in Cancer Patients)—are assessing durations of therapy of ≤ 6 months …”
Section: Current Controversies In Catmentioning
confidence: 99%